Challenges with sensitized recipients in pediatric heart transplantation (Clinics, 2014)
The sensitization of patients to human leukocyte antigens prior to heart transplantation is increasingly being recognized as an important challenge both before and after the transplant, and the effects of sensitization on clinical outcomes are just beginning to be understood. Many patients are listed with the requirement of a negative prospective or virtual crossmatch prior to accepting a donor organ. This strategy has been associated with both longer waitlist times and higher waitlist mortality. An alternative approach is to transplant across a potentially positive crossmatch while utilizing strategies to decrease the significance of the human leukocyte antigen antibodies. This review will examine the challenges and the impact of sensitization on pediatric patients prior to and following heart transplantation.